Metaverse vs Classroom: A Quasi-Experimental Study on Learning Digital Business and Creative Skills - Hanif Ksatria Faza; Btari Mariska Purwaamijaya; Muhammad Dzikri Ar Ridlo (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
To address the need for practical skills in the creator economy era, this study evaluates the comparative effectiveness of Metaverse Based Learning, Online Learning, and Blended Learning models on students' cognitive competence. This study fills a crucial research gap by providing a quasi-experimental comparison within a developing country context, where technical constraints are a critical variable. Employing a mixed-methods approach anchored in a quasi-experimental pretest-posttest non-equivalent control group design (N = 90), data were collected using a validated cognitive competency test (α = 0.796) administered as a pre/post-test, supplemented by participant observation and semi-structured interviews. Quantitative data were analyzed using N-Gain and ANCOVA, while qualitative data were analyzed thematically. The results revealed a paradox: quantitatively, there was no statistically significant difference (p = .376) among the groups, with all models proving equally effective (N-Gain